A new framework for short-term wind power probability forecasting considering spatial and temporal dependence of forecast errors - Sun, Yong; Li, Baoju; Hu, Wenhui; Li, Zhenyuan; Shi, Chaoyu (Frontiers in Energy Research, 2022)
The Since deterministic prediction errors of wind power cannot be avoided, probabilistic prediction can adequately describe the uncertainty of wind power and thus provide further guidance to dispatching authorities for decision making. Current probabilistic prediction methods for wind power are still incomplete in mining its physical variation process. Therefore, this paper constructs a new framework for short-term wind power probabilistic forecasting considering the spatio-temporal dependence of errors by mining the spatio-temporal characteristics of historical wind power data and numerical weather forecasts at numerical weather prediction (NWP). Firstly, the deterministic prediction results are obtained by an improved deep belief network (DBN); then, a multi-location NWP is introduced to propose a multi-level error scenario partitioning method considering the spatio-temporal dependence property. Finally, a new error sample set is formed by reconstructing the kernel density estimation method to adapt the modeling, and the short-term wind power probability prediction at different confidence levels is carried out. It is thus concluded that the effectiveness of the overall framework under the probabilistic prediction considering spatio-temporal dependence is verified in a wind farm in Jilin, China, and the prediction accuracy is effectively and significantly improved compared with the same confidence level, and the coverage of the evaluation index prediction interval is improved by 1.23%, 0.72%, and 0.80%, and the average bandwidth of the prediction interval is reduced by 2.14%, 1.40%, and 0.63%, which confirms the proposed the effectiveness and feasibility of the method.